3D Dendritic Nanostructure of Silver‐Array: Preparation, Growth Mechanism and Application in Nitrate Sensor. Issue 2 (24th January 2013) - Hu, Jingfang; Sun, Jizhou; Bian, Chao; Tong, Jianhua; Shanhong, Xia
Abstract A 3D dendritic nanostructure of silver‐array (DSA) was prepared via electrodeposition on an interdigitated array (IDA) microelectrode. For preparation of this nanostructure, the optimal parameters such as deposition potential, deposition time, the electrode bandwidth and gap size were systematically investigated. It was found that the edge effect of the IDA microelectrode is a key factor for controlling the 3D dendritic growth of silver. Furthermore, the formation of the 3D dendritic morphology was discussed from the aspect of electrochemical nucleation theory and nonequilibrium growth dynamics to give a deep understanding of its growth mechanism. For its potential practical application, we showed that the as‐prepared 3D DSA nanomaterial exhibited high electrocatalytic reduction ability to nitrate in neutral solution and excellent performance for nitrate determination. An amperometric nitrate microsensor based on the 3D DSA was obtained.